2009
DOI: 10.1002/rcs.286
|View full text |Cite
|
Sign up to set email alerts
|

Advances in collision detection and non‐linear finite mixed element modelling for improved soft tissue simulation in craniomaxillofacial surgical planning

Abstract: The experimental results support the novel methodological advancements in collision detection and biomechanical modelling proposed in this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
1
1
Order By: Relevance
“…The bone failure criterion used in this study was the maximum main stress, with the critical value range reported in the literature of 0.13-0.34 MPa. Although current articles suggest the use of maximal deformation as the criterion of bone failure, results differing from those obtained in the present study would only be possible with models containing more elaborate materials than the linear elastic model used herein (16,19,(27)(28)(29).…”
Section: Discussioncontrasting
confidence: 73%
“…The bone failure criterion used in this study was the maximum main stress, with the critical value range reported in the literature of 0.13-0.34 MPa. Although current articles suggest the use of maximal deformation as the criterion of bone failure, results differing from those obtained in the present study would only be possible with models containing more elaborate materials than the linear elastic model used herein (16,19,(27)(28)(29).…”
Section: Discussioncontrasting
confidence: 73%
“…For the multiarm robot for mandible reconstruction surgery with three arms, its workspace is adjusted to the size of patient's head. Due to the overlap of the workspaces of each arm, the interference is prone to happen, causing a collision [30]. Based on the LSS (Linearly Swept Sphere) linear scan ball model of the rod, the collision avoidance motion control was researched by C-space model, the C-space mapping of obstacle, and improved heuristic A * search algorithm in order to guarantee the surgery safety.…”
Section: Conclusion and Discussionmentioning
confidence: 99%